Curriculum needs of George Washington Senior High School, Guam - Buchzik, Louise M. (s.n.], 1970)
The major problem of the study is to find out the needs of George Washington Senior High School in Guam, as viewed by the professional staff of the school. The study concerns itself mainly with the present curriculum and courses of study offered to the students, and analyzes its curriculum in an effort to determine if it meets the needs of the students and if the school offers an adequate foundation for the students' educational development in whatever occupation or profession the students choose.